EXPERIENCE OF INITIATING MICROVASCULAR SURGERY WITH LIMITED RESOURCES - Farooqui, Aamna Sanober; Shahzad Shaikh; Pirzada, Samra Irshad; Zaheer Ahmed Qasmi (Journal of Ayub Medical College Abbottabad, 2024)
<!–StartFragment–> Background: Microvascular surgery is an imperative part of reconstructive armamentarium. At times, reconstructing a post-surgical or post traumatic defect is not potentially possible with loco-regional flaps and good function and aesthetics can be achieved with free tissue transfer. For last few decades, the revolutionary microvascular reconstructive techniques have brought a paradigm in the field of plastic surgery, rendering major debilitating defects to be dealt with, which were previously considered inoperable. Methods: This study is conducted at the department of Plastic Reconstructive surgery, Liaquat University of Medical and Health Sciences, Jamshoro from February 2022 to July 2023. The aim of this study is to share our experience and lessons learnt initiating microvascular surgery at a tertiary care center in the city of Hyderabad, Pakistan. <!–EndFragment–>